2022
DOI: 10.4236/abb.2022.139028
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Semen Quality and Fertility of Red Chittagong Cattle, BCB1 and Munshiganj Bulls of Bangladesh

Abstract: The present study was conducted to analyze the fresh and post-thaw semen quality and fertility from native bulls of Red Chittagong Cattle (RCC), BLRI Cattle Breed 1 (BCB1), and Munshiganj Cattle of Bangladesh. One hundred and seventy-two ejaculates were collected by artificial vagina set and semen analysis was performed using Computer Assisted Sperm Analyzer (CASA) at Bangladesh Livestock Research Institute. Commercial extender (AndroMed) was used to dilute the fresh semen. After equilibration (4˚C for 4 hr), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 30 publications
5
5
1
Order By: Relevance
“…In the current study, average sperm concentration was found 1510.27 ± 844.07 million/ml which was similar with the findings in Munshiganj bull (1669.60 ± 192.07 million/ml) [ 48 ]and (1796 ± 122.29 million/ml) [ 56 ]. The present study findings was much higher than the report of [ 54 ] (907.39 ± 23.01 million/ml in RCC bull), and (1035.24 ± 279.79 to 1088.12 ± 297.14 million/ml) in Bali bull in Indonesia [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, average sperm concentration was found 1510.27 ± 844.07 million/ml which was similar with the findings in Munshiganj bull (1669.60 ± 192.07 million/ml) [ 48 ]and (1796 ± 122.29 million/ml) [ 56 ]. The present study findings was much higher than the report of [ 54 ] (907.39 ± 23.01 million/ml in RCC bull), and (1035.24 ± 279.79 to 1088.12 ± 297.14 million/ml) in Bali bull in Indonesia [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Semen quality can be affected by a wide range of genetic and environmental factors including bull age, collection interval, collection frequency, and season [ [45] , [46] , [47] ]. Regarding semen volume, present findings are in consistent with the findings 4.93 ± 0.15 ml in Munshiganj bull [ 48 ] and 4.88 ± 1.55 to 6.25 ± 1.43 ml/ejaculate in Bali bull in Indonesia [ 49 ]. On the other hand, 5.08–6.00 ml/ejaculation were reported for BLRI cattle breed-1 [ 50 ].…”
Section: Discussionsupporting
confidence: 90%
“…In swamp buffalo, there were significant differences in the age of buffalo on dose/ejaculates and 7 years bull produced more dose/ejaculate than 5 and 6 years of bull [21]. The quantity of frozen semen dose produced by the experimental bull in this experiment is within the standard range (349.01 dose/ejaculate) of mature RCC bull [20]. However, the total number of frozen semen production depends on management, freezing process, collection frequency, nutrition, and other factors.…”
Section: Discussionmentioning
confidence: 50%
“…The kinematic properties of fresh and frozen semen did not vary significantly among the different age groups of RCC bulls. Different kinematics properties of younger and older bulls are almost similar to the range of mature RCC bulls [20].…”
Section: Discussionmentioning
confidence: 71%
“…The volume of semen of Pesisir cattle ranged from 2 ml to 4 ml. This result is lower than the semen of Munshiganj cattle which ranges up to 4.93 ml (Hossain et al, 2022), however it is higher than the other local cattle such as Bali cattle which has an average of 3.4 ml (Susilawati et al 2018). Low or high volume does not cause harm, but if the concentration is low, it will cause a limited number of spermatozoa in one ejaculate (Wafa et al, 2010).…”
Section: Quality Of Fresh Pesisir Cattle Semenmentioning
confidence: 83%